2009
DOI: 10.1051/kmae/2009014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on the nutritive value of the natural food of three omnivorous fish (Oreochromis niloticus,Sarotherodon galilaeus,Citharinus citharus) in Batamani Pond (Mali, West Africa)

Abstract: Key-words: omnivorous fish, natural food, nutritive value, climate, Batamani Pond, MaliThe chemical composition of the stomach contents and the digestibility of organic matter, proteins and energy of three planktivorous fish species (Oreochromis niloticus, Sarotherodon galilaeus and Citharinus citharus) were studied in Batamani Pond (Mali, West Africa) during the dry and wet seasons. The diet contents of O. niloticus and S. galilaeus presented high levels of organic matter and proteins during the wet season (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…This is confirmed by the low digestibility of organic matter (32-37%) and amino-acids (40-50%). The values are comparable to those observed in the batamani pond (Ble and Arfi, 2009) and for the same species in other Ethiopian lakes (Getachew, 1987(Getachew, , 1993.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is confirmed by the low digestibility of organic matter (32-37%) and amino-acids (40-50%). The values are comparable to those observed in the batamani pond (Ble and Arfi, 2009) and for the same species in other Ethiopian lakes (Getachew, 1987(Getachew, , 1993.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results on the abiotic parameters were shown in pond of Batamani, a shallow pond in the Inner Niger Delta of Mali. Hydrobiological characteristics of this pond were subject to a very marked seasonal influence (Blé and Arfi, 2009). In the lake Ziway of Ethiopia, Getachew and Abebe (1992) found that the low organic matter content of water was related to the low primary productivity due to turbidity caused by runoff during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations